Overburden destruction structure model and mechanism of mine pressure in Caojiatan coal mine with 10 m super large mining height - Zhen ZHANG; Zhizeng HUANG; Xiaogang LIU; Jianchao REN; Qianjin LIU; Xingyu LIN; Jisheng XUE; Rongshan MA (Meitan xuebao)
The successful mining of 10 m ultra-high working face in Caojiatan coal mine marks a new level of full height mining technology in China’s extra-thick coal seam. Based on the pressure, displacement and energy sensors, the mining of ultra-high mining face is monitored comprehensively, the characteristics of mine pressure behavior were clarified, the law of migration and fracture of overlying strata were obtained,the overburden structure model of ultra-high space mining under multi-layer thick and hard roof was established, and the mechanism of mine pressure action was clarified. The results show that: 10 m ultra-high mining height mining overburden has a large space of breaking, strong mine pressure, and features of “large compression step interval, obvious dynamic load, large shrinkage under support, and high safety valve opening rate”. The periodic pressure step is mainly 10～25 m, with an average of 17.8 m, an increase of 5.2%～21% compared with the same wing full-mechanized caving mining. The maximum dynamic load coefficient of periodic pressure is 1.44～1.68, with an average of 1.60, and the proportion above 1.6 is 63%, which increases by 60% compared with the same wing full-mechanized caving mining. The maximum reduction of the support is concentrated in the range of 0.4～1.0 m, with an average of 0.63 m. The opening rate of the hydraulic support safety is 10.6%～78.9%, and the opening rate of the safety valve is more than 50% during the pressure period is 48.1%. The pressure region of the working face is obvious, which is concentrated in the range of 75 ～ 250 m from the head,with the characteristics of “large and small period to pressure, and multiple continuous large periodic weighting”. The interval of large periodic weighting is 102～186.8 m, with an average of 137.5 m. The microseismic events are distributed along the strike direction in the range of 300 m before and after the working face. During the large period to pressure, the micro-seismic high-energy events are concentrated in the layer 20 m, 50 m, 80 m above the coal seam. The energy-accumulating layers change in a “low-high-low” reciprocating cycle along the working face, and are distributed in a wave-like manner. The overlying rock strata are in a long-distance suspended state behind the goaf, and the thick hard rock strata in the middle and upper parts have synchronous linkage fracture characteristics, resulting in large-cycle pressure on the working face. The expansion of the stress arch is affected by the hard top roof, the longitudinal development of the stress arch is temporarily interrupted, and the lateral span increases, forming an “arch-beam” structure with semi-arches at the front and rear ends and a beam in the middle. The overburden strata are mined in the ultra-high mining face under multi-layer thick hard roof, showing a superimposed “arch-beam” structure. The lower “arch-beam” breaks cause small-cycle pressure, and the rock blocks are in step-like contact after the break. The middle and upper “arch-beam” breaks cause large-cycle pressure, and its continuous breakage causes multiple continuous large periodic pressure, and the rock blocks are in an articulated state after the break.The support strength required for the sliding and rotary deformation instability of the middle main control bearing layer II and the high main control bearing layer III is 2.32～ 2.90 and 1.91～2.14 MPa, respectively. The existing support equipment is difficult to effectively control the surrounding rock of the working face.The research results have important guiding significance for the surrounding rock control in ultra-large mining height.